2012
DOI: 10.1111/j.1365-2893.2012.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis C on survival in dialysis patients: a link with cardiovascular mortality?

Abstract: Summary.  Recent evidence has been accumulated showing that anti‐HCV‐positive serologic status is significantly associated with lower survival in dialysis populations, but the mechanisms underlying this negative relationship are still unclear. The aim of this study was to conduct a systematic review of the published medical literature concerning the impact of hepatitis C virus (HCV) infection on all‐cause and disease‐specific mortality of patients on regular dialysis. The relative risk of all‐cause, cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
138
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(142 citation statements)
references
References 32 publications
3
138
0
1
Order By: Relevance
“…The prevalence rate of HCV among patients undergoing hemodialysis within a U.S. hemodialysis network was reported as 7.8 percent (range: 5.5 to 9.8 percent) (Finelli, Miller, et al 2005), and it is estimated that more than 60,000 HCV-infected patients will require hemodialysis by 2020 (Butt, Wang, et al 2011). A significant relationship has been observed between HCV infection and increased mortality among patients on long-term dialysis (Fabrizi, Dixit, et al 2012).…”
Section: Patients With Advanced Chronic Kidney Diseasementioning
confidence: 95%
“…The prevalence rate of HCV among patients undergoing hemodialysis within a U.S. hemodialysis network was reported as 7.8 percent (range: 5.5 to 9.8 percent) (Finelli, Miller, et al 2005), and it is estimated that more than 60,000 HCV-infected patients will require hemodialysis by 2020 (Butt, Wang, et al 2011). A significant relationship has been observed between HCV infection and increased mortality among patients on long-term dialysis (Fabrizi, Dixit, et al 2012).…”
Section: Patients With Advanced Chronic Kidney Diseasementioning
confidence: 95%
“…24 Studies have consistently shown that HCV infection is associated with an increased mortality in patients with ESRD. [25][26][27][28][29] In a meta-analysis by Fabrizi et al, 26 the relative risk of mortality was 1.35 (95% confidence interval, 1.25 to 1.47) among HCV-infected patients with ESRD. Analysis of cause-specific death showed an increased burden of cardiovascular risk, supporting the concept that HCV is a systemic disease with important extrahepatic consequences.…”
Section: Hcv In Patients With Kidney Diseasementioning
confidence: 99%
“…Analysis of cause-specific death showed an increased burden of cardiovascular risk, supporting the concept that HCV is a systemic disease with important extrahepatic consequences. 26 Of interest, transplanting an anti-HCVpositive patient with ESRD is accompanied by a significantly decreased risk of death compared with remaining on the waiting list. This survival benefit is largely attributable to a decrease in cardiovascular events within the first year post-transplant.…”
Section: Hcv In Patients With Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Patients on maintenance hemodialysis with HCV continue to have higher mortality rates compared to those without HCV (3). Fortunately, the advent of well tolerated oral regimens for HCV has expanded the treatment strategies in patients with severe CKD and hemodialysis.…”
mentioning
confidence: 99%